PENGARUH INTELLECTUAL CAPITAL DAN PENGUNGKAPANNYA TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN FARMASI DI BEI) - JESSIKA OKTAVIA S. JACUB (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Intellectual capital is an intangible asset used to improve corporate performance and corporate value creation. Disclosure of intellectual capital is a report issued by a company to give information for those who are not involved directly in the company. The purpose of this research are to examine the effect of intellectual capital and disclosure of intellectual capital on firm value in the pharmaceutical company listed on the Indonesia Stock Exchange (BEI). This research used independent variables of intellectual capital and disclosure of intellectual capital and the dependent variable is firm value. The sampling method used is the census since the population is the sample, which are 9 companies as the sample. This research was conducted in the period 2006-2010. Analysis of the data used is multiple linear regression with hypotheses testing of statistic F and t tests. The results of this research showed that (1) intellectual capital have a significant positive effect on firm value that suggest that intellectual capital is a power source of companies to compete in achieving competitive advantage and increase market perceptions of firm value, and (2) disclosure of intellectual capital have a significant positive effect on firm value that suggest that disclosure of intellectual capital becomes the key for value creation